STUDY OF THE IMPACT OF CLIMATE CHANGE AT THE SOCIAL LEVEL IN UTTAR PRADESH - Yadav, Kunwar Vishal Pratap; Pachauri, Suruchi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The impacts of climate change are not limited to environmental problems in Uttar Pradesh but also have wide social and cultural implications. Given the huge population and diverse social structure of the state, climate change has had a serious impact on various aspects of life. It is not only affecting the livelihood of the people but also has a profound impact on their social fabric and cultural heritage. The rural areas of Uttar Pradesh are the worst affected by climate change. Agriculture is the main livelihood of the state and incidents like drought, flood, and erratic rainfall have made the condition of farmers extremely miserable. Due to failure in farming, farmers and their families are facing economic crisis. This economic crisis is causing stress and instability in society, affecting family and community relations. Suicides have also increased, which has become a serious problem in society. The impact of climate change on women and children is particularly worrying. Due to the water crisis, women are spending more time and energy fetching water, which has reduced their participation in education and other social activities. Children's health is also being affected, as the incidence of malnutrition and waterborne diseases has increased. This is also affecting education, as children's attendance in school is decreasing due to diseases.